Long-term locked knee ankle foot orthosis use: A perspective overview of iatrogenic biomechanical and physiological perils - Ghoseiri, Kamiar; Zucker-Levin, Audrey (Frontiers in Rehabilitation Sciences, 2023)
A knee ankle foot orthosis (KAFO) may be prescribed to the person with severe neuromusculoskeletal impairment of the lower limb to promote walking stability. The locked knee ankle foot orthosis (L-KAFO) is among the KAFO’s routinely prescribed; however, long-term use of the L-KAFO is associated with musculoskeletal (arthrogenic and myogenic) and integumentary changes, and gait asymmetry with increased energy expenditure. Consequently, the risk of developing low back pain, osteoarthritis of the lower limbs and spinal joints, skin dermatitis, and ulceration increases, all of which impact quality of life. This article synthesizes the iatrogenic biomechanical and physiological perils of long-term L-KAFO use. It promotes using recent advances in rehabilitation engineering to improve daily activities and independence for proper patient groups.